Stevenson's Scheme and People's Rubber Exports at Labuhan Bilik Harbor, 1922-1928 - Edi Sumarno; Junita Setiana Ginting; Nina Karina; M. Azis Rizky Lubis (Budapest International Research and Critics University, 2020)
This paper discusses the policy of unilaterally limiting rubber exports by the UK with the so-called Stevenson's Scheme for smallholder rubber exports through Labuhan Bilik Harbor. The limitation scheme that took place during the 1922-1928 period was implemented by the UK for the phenomenon of the decline in world rubber prices after World War I. England, whose colonies dominated world rubber exports, hoped that the Netherlands would join in this plan to restrict exports. However, the Dutch refused. This decision brought blessings to the Dutch Indies rubber producers, including in Labuhan Batu with its main port of Labuhan Bilik. These port export figures show an increase over the period that Stevenson's Scheme was applied. Even so, the question is, is it true that the increase in smallholder rubber exports through Labuhan Bilik Harbor was caused by the application of Stevenson's Scheme? Or, are there other factors that need to be considered around the increase in exports in that period? This descriptive-analytic study attempts to answer these questions using colonial sources. The sources used in this paper are in the form of colonial reports, such as the Colonial Verslag, the Report of the Dutch Indies People's Rubber Inquiry Commission, the Dutch Indies People's Rubber Periodic Report, the Job Handover Report, and other literature sources.